2018
DOI: 10.5130/ajceb.v18i3.5885
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors influencing performance outcome of joint venture construction projects in South Africa: Comparison of first and second order models

Abstract: Joint ventures (JVs) have become increasingly common, because of the complexity and challenges associated with the delivery of construction projects globally and in South Africa. However, it has been established that JV projects have experienced unsatisfactory performance leading to clients’ dissatisfaction. The purpose of this paper is therefore to determine the critical success factors (CSFs) influencing the performance of JV construction projects in South Africa. A positivist philosophy position was adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Therefore, a good working relationship with clients, contractors and subcontractors is equally important to good working relationship with superiors, co-workers and design team members. In a similar vein, Mba and Agumba (2018) also found that a long-term working relationship demonstrated via commitment from parties involved in the project fails to influence construction project outcome.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, a good working relationship with clients, contractors and subcontractors is equally important to good working relationship with superiors, co-workers and design team members. In a similar vein, Mba and Agumba (2018) also found that a long-term working relationship demonstrated via commitment from parties involved in the project fails to influence construction project outcome.…”
Section: Resultsmentioning
confidence: 86%
“…Good working relationship is also reflected through the commitment amongst project participants. Mba and Agumba (2018) proposed that commitment amongst project participants is important to ensure successful project performance. However, the working relationship amongst project participants is typically problematic and generates adverse effect to project performance (Kärnä and Junnonen, 2017).…”
Section: Working Relationshipmentioning
confidence: 99%
“…In the literature on project management, CSFs have been investigated in a wide variety of contexts and applications and in different sectors, such as construction industry (Nursin & Latief, 2018;Tsiga et al, 2016;Yan et al, 2019), aviation industry (Adabavazaeh & Nikbakht, 2019), information technology (Adzmi & Hassan, 2018;Ghayyur et al, 2018), service industry (Yang & Yang, 2018), medical technology (García-Villarreal et al, 2019), renewable-energy industry (Maqbool et al, 2018), as well as in general projects (Liu et al, 2018;Mba & Agumba, 2018) and in the fields of management and entrepreneurship (Martens et al, 2018;Silva et al, 2018).…”
Section: Critical Success Factors and Project Management Performancementioning
confidence: 99%
“…Some studies investigated critical factors in Construction projects in general (Santoso and Gallage, 2019). Other body of literature studied critical factors in Joint venture construction projects (Mba and Agumba, 2018), or Home building construction (Zehro and Jkhsi, 2020), or road construction projects (Kisavi and Ngugi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%